กลวิธีการประพันธ์ในงานเขียนบทสัมภาษณ์ของวรพจน์ พันธุ์พงศ์ - สุขาว พัชรา; สุวัธนวนิช พรธาดา; บุญประเสริฐ พิมพาภรณ์ (บรรณศาสตร์ มศว, 2014)
จากการศึกษากลวิธีการประพันธ์ในงานเขียนบทสัมภาษณ์ของวรพจน์ พันธุ์พงศ์ พบลักษณะเด่น 7 ประการ ประการที่หนึ่ง การตั้งชื่อเรื่อง พบ 5 กลวิธี ได้แก่ การตั้งชื่อเรื่องแบบบอกเนื้อหาเชิงสรุป แบบชวนฉงน แบบขัดแย้ง การตั้งชื่อเรื่องจากสิ่งที่เป็นกระแสสังคม และแบบคำถาม ประการที่สอง การเขียนความนำ พบ 10 กลวิธี ได้แก่ การกล่าวถึงภูมิหลังของผู้ให้สัมภาษณ์ แบบสนทนากับผู้อ่าน แบบนำด้วยเหตุการณ์ที่เป็นกระแสสังคม แบบเรื่องสั้นและนวนิยาย แบบนำด้วยเรื่องเล่าที่ผู้เขียนได้ประสบมา แบบบทละคร แบบกระแสสำนึก แบบนำด้วยการสร้างปมขัดแย้ง แบบกลอนเปล่า และนำด้วยคำพูดของผู้ให้สัมภาษณ์ ประการที่สาม การเขียนเนื้อเรื่อง พบการนำเสนอจากกลวิธีการตั้งคำถาม 8 ลักษณะได้แก่ การถามเพื่อเปิดประเด็น การถามด้วยคำถามต่อเนื่อง การถามในลักษณะสรุปคำตอบ การถามโดยแสดงทัศนะของผู้เขียน การถามโดยกล่าวอ้างแหล่งที่มา การถามโดยพาดพิงถึงบุคคลที่สาม การถามในลักษณะยั่วยุอารมณ์ และการถามด้วยคำถามแย้ง ประการที่สี่ การนำเสนอฉากและบรรยากาศ พบการนำเสนอฉากที่เป็นสถานที่ เวลา และวิถีชีวิตหรือสภาพสังคม ประการที่ห้า การปรากฏตัวของผู้เขียนในบทสัมภาษณ์ พบทั้งการแสดงตัวตน และการแทรกทัศนคติของผู้เขียน ประการที่หก การเสนอบทสัมภาษณ์ของบุคคลอื่นประกอบ ประการที่เจ็ด การเขียนความจบ พบ 5 กลวิธี ได้แก่ การจบด้วยถ้อยคำให้สัมภาษณ์ การกล่าวถึงบุคลิกภาพของผู้ให้สัมภาษณ์ การทิ้งท้ายไว้ให้คิด การแสดงความรู้สึกของผู้เขียน และการบรรยายฉากและบรรยากาศ The researcher analyzed writing techniques used by Worapoj Punpong in his interview articles, as well as to categorize perspectives presented in his works. The results showed that there were seven distinctive writing techniques usually used by the writer. Firstly, in writing the titles of the interview articles, the researcher found five technigues : (1) showing the main idea in the titles, (2) making readers wonder, (3) showing controversies, (4) presenting social hot issues, and (5) asking questions. Secondly, in the leading part of the interview articles, Worapoj used 10 techniques: (1) introducing the story by describing interviewees’ backgrounds, (2) talking with readers, (3) discussing social issues, (4) using short story and novel writing techniques, (5) telling about writer’s experiences, (6) using dramatic plots, (7) showing stream of consciousness, (8) leading with conflicts, (9) using free verse or interviewees’ phrases, and (10) starting the articles with interviewees’ descriptive expressions. Thirdly, eight types of questions were found in using in the main content: (1) leading, (2) follow-up, (3) information-checking, (4) reflective, (5) information sources, (6) third persons referring, (7) asking as provocation and, (8) stating counter evidence. Next, the writer presents places, times and life styles or social situations as the settings. Fifth, in the matter of Worapoj’s self-presentation, the author showed himself as a part of the story, and sometimes expressed his own opinions on discussing issues. Sixth, he occasionally used opinions from people get involved with the interviewee to fulfill the story. Lastly, in the ending part, Worapoj finalized the stories in five techniques : (1) using interviewees’ opinions (2) applying interviewees’ personality, (3) leaving questions, (4) expressing author’s feelings, and (5) narrating settings or environments.